ENVIRONMENTALMONITORING SYSTEMS AIMED AT DEVELOPING PROTOCOLS FOR HUMAN HEALTH - Brunetti, Luana Serafina; Angelone, Tommaso; Indiveri, Cesare; La Russa, Mauro Francesco (Università della Calabria, 2025)
Plastic pollution is one of the main global environmental problems of the 21st century. Through the course of the rivers, most plastic waste ends up in the sea, where a slow degradation determines its fragmentation into smaller particles, commonly known as microplastics (MPs) and nanoplastics (NPs). The main problem of the permanence of microplastics in the seas is their ability to interact with aquatic organisms, thus entering the food chain and reaching humans through the consumption of contaminated fish. The toxicity of microplastics is mainly linked to the fact that, during their permanence in the ecosystem, they can absorb and become a vehicle of harmful substances to humans, including pathogenic microorganisms, drugs, antibiotics, and heavy metals. As for heavy metals, some of them are indispensable for normal human biochemical processes, but others, such as lead and mercury, are extremely toxic. SoLute Carriers (SLCs) represent the main target of heavy metals due to their localization on the cell surface. In particular, relevant importance are the organic cation transporters that form a subfamily of the larger SLC22 family because, in addition to the physiological role of transporting endogenous organic cations, are crucial in the disposition of drugs and the interaction with xenobiotics. Among these transporters, OCTN1 appeared in vertebrates during evolution and has homologs in some fishes. Interestingly, OCTN1 harbours seven cysteine residues, already known as a target of a prototype heavy metal, namely mercury chloride. The following study aims to analyze microplastics sampled on the surface of the Mediterranean Sea in six particularly polluted areas of the Calabrian coasts. The size, shape, color, and polymeric composition of the samples have been investigated. Most of the microplastics were very small, with shape and color critical for interactions with biota. In addition, the presence of heavy metals potentially harmful to humans was detected. Subsequently, one of the most important freshwater fish species in the human diet (Oncorhynchus mykiss) has been used as a model for studying the release of these metals from microplastics by the simulation of its digestion process. Interestingly, the release from microplastics of chromium, lead, cadmium, and zinc was significant, especially during the gastric phase of the digestive process, due to the very acidic pH. Lead was also detected by SP-ICP-MS, probably due to solid deposits on the surface of the plastics. Furthermore, the powder obtained from some reference plastic materials showed that the amount of metals released depends on the size of the microplastics and, consequently, on the surface area exposed to the digestive fluids. Finally, the effect of these heavy metals on the human organism was evaluated through interaction studies with the organic cation transporter OCTN1. The potency of heavy metals on OCTN1 was evaluated through IC50 analysis, using the experimental system of the proteoliposome, and the values were in the micromolar range. In addition, the mechanism of interaction of these xenobiotics with the protein was elucidated through site-directed mutagenesis and computational analyses. To suggest some potential scavengers, the effects of some reducing agents were studied. Some of these can reverse the negative effects of heavy metals on OCTN1.
UNIVERSITA’ DELLA CALABRIA Dipartimento di Biologia, Ecologia e Scienze della terra (DiBEST) Dottorato di Ricerca in Life Science and Technology, Ciclo XXXVII
Keywords: microplastics; heavy metals; ICP-MS; SLC22A4; liposomes